(3LZQGajI GdSjGSI s - (3CMeO GdOdjej(B, (3UHMjs; (3YGQa YHO GdQRGb, YHO GdSdGes; (3YdcI QRjc GdcHjSj, YHO Gddgs ((3YeGfs (3EHUGQ fGTQhf hehRYhf s, 2022)
(3eONd Edi LZQGajI GdSjGSI heaghegG, GgJeGeGJ heYGdLI GdLZQGajG GdSjGSjI, LZQGajI GdSjGSI YHQ GdJGQjN, fTCI GdLZQGajG GdSjGSjI, JYQjaGJ GdLZQGajG GdSjGSjI, WQGFb GdHMK aj GdLZQGajI GdSjGSjI, YdGbI GdLZQGajI GdSjGSjI HGdYdhe GdCNQi, Yde GdSjGSI hLZQGajI GdSjGSI hefGgL GdHMK ajgeG, GdLZQGajG GdSjGSjI hYde GdLZQGajG, GdLZQGajG GdSjGSjI hYde GdJGQjN, GdLZQGajG GdSjGSjI hGdYdhe GdSjGSjI, GdLZQGajG GdSjGSjI hYde GdYdGbGJ GdOhdjI, Yde GdLjhHhdJjc hGdfXQjGJ GdLjhSJQGJjLjI, JYQja GdLjhHhdjJjc, fXQI JGQjNjI ddLjhHhdJjc, eYGjjQ GdJaQbI Hjf GdLZQGajI GdSjGSjI hGdLjhHhdJjc, GdCSS GdQFjSjI dYde dYde GdLjhHhdJjcS, CfeGW GdOQGSGJ GdLjhHhdJjcjI, GdfXGe GdLjhHhdJjcj hYfUQ GdeaGLCI, GdLjhSJQGJjLjI hGdLjhHhdJjc, eaghe GdOhdI, JYQHa GdOhdI GdMOjK, eaghe GdOhdI cMbjbI SjGSjI, CQcGf hechfGJ GdOhdI GdMOjKI, UdGMjGJ GdOhd, YhGed bhI GdOhdI GdWHjYjI hGdHTQjI, GdYdGbGJ GdOhdjI heaghe GdbhI, CfhGY GdbhI, ebheGJ GdbhI aj LeghQjI GdUjf GdTYHjI (B((3GfehPLG(B)(3, GdJejjR Hjf eaghej (B"(3GdSjGSI GdOhdjI(B" (3h(B"(3GdYdGbGJ GdOhdjI(B"(3, eaghe GdbhI hNUGFUg, eaghe GdbhI GdfGYeI, GdaQb Hjf GdbhI GdfGYeI hGdbhI GdPcjI, eaghe GdbhI GdPcjI hTQhWgG, GdbhI GdEdcJQhfjI hGdJaGYdGJ GdOhdjI, eaghe GdaVGA GdEdcJQhfj, UQGY Ch UOGe GdMVGQGJ(B.s
Keywords: (3GdLZQGajG GdSjGSjI(B- (3GdJcfhdhLjGs; (3GdMOhO GdSjGSjI s